Monoolein-based nanocarriers for enhanced folate receptor-mediated RNA delivery to cancer cells - Lopes, Ivo (2016)
We report the development and characterization of a novel nanometric system for specific delivery of therapeutic siRNA for cancer treatment. This vector is based on a binary mixture of the cationic surfactant dioctadecyldimethylammonium chloride (DODAC) and the helper lipid monoolein (MO). These liposomes were previously validated by our research group as promising non-viral vectors for nucleic acid delivery. In this work, the DODAC:MO vesicles were for the first time functionalized with polyethylene glycol and PEG-folate conjugates to achieve both maximal stability in biological fluids and increase selectivity toward folate receptor α expressing cells. The produced DODAC:MO:PEG liposomes were highly effective in RNA complexation (close to 100%), and the resulting lipoplexes also demonstrated high stability in conditions simulating their administration by intravenous injection (physiological pH, high NaCl, heparin and fetal bovine serum concentrations). In addition, cell uptake of the PEG-folate-coated lipoplexes was significantly greater in folate receptor α positive breast cancer cells (39% for 25 µg/mL of lipid and 31% for 40 µg/mL) when compared with folate receptor α negative cells (31% for 25 µg/mL of lipid and 23% for 40 µg/mL) and to systems without PEG-folate (≈13% to 16% for all tested conditions), supporting their selectivity towards the receptor. Overall, the results support these systems as appealing vectors for selective delivery of siRNA to cancer cells by folate receptor α-mediated internalization, aiming at future therapeutic applications of interest.